Influence of a B16/F10 melanoma variant on the Вcl-2 levels in mitochondria in various organs of female mice - O. I. Kit (Bûlleten' Sibirskoj Mediciny, 2021)
Aim. To study the Bcl-2 level in mitochondria of various organs in female mice with standard and stimulated growth of an experimental B16/F10 melanoma.Materials and methods. The study included С57ВL/6 female mice (n = 168). The experimental animals were divided into the following groups: an intact group (n = 21), a group with modelled chronic neuropathic pain (CNP) (n = 21), an M group with B16/F10 melanoma (n = 63), and a CNP + M group (n = 63). The Bcl-2 concentration (ng / mg protein) in mitochondrial samples was determined by ELISA (Thermo Fisher Scientific, Austria). Statistical analysis of the results was carried out using Statistica 10.0.Results. Compared to the Bcl-2 levels in the intact animals, CNP decreased this parameter in the cardiac mitochondria by 1.3 times, while increasing it by 5.9 times in the skin mitochondria. In the dynamics of standard melanoma growth, the Bcl-2 content changed compared with the corresponding intact values in the mitochondria of the brain, heart, and skin, but did not change in the liver and kidneys. In the mitochondria in melanoma, the Bcl-2 levels were high throughout the entire period of standard tumor growth in comparison with the intact skin. The stimulated melanoma growth in CNP was involving more organs into the pathological process as the tumor was growing. Thus, in comparison with the values in the CNP group, the mitochondrial Bcl-2 levels changed in the heart at week 1; in the heart and skin – at week 2; in the heart, skin, and brain – at week 3. The Bcl-2 levels did not change in the liver and kidney mitochondria. In the mitochondria in the CNP-stimulated melanoma, the Bcl-2 levels were lower than in the skin mitochondria in CNP throughout the entire tumor growth period.Conclusion. The liver and kidney mitochondria are somewhat Bcl-2 stable in both standard and stimulated tumor growth. It is assumed that different Bcl-2 dynamics in the mitochondria in melanoma depending on the variant of tumor development reflects the modulating effect of CNP and the ability to change the Bcl-2 levels according to the growth phase.